Pengendalian Kualitas Guna Meminimalisir Deffect dengan Pendekatan Metode Seven Tools Produk Seat Cover Jok Mobil Perusahaan Bekleed (Studi Kasus: CV. XYZ) - Syahputra, Nugraha Yuga; Nuha, Hilyatun (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Quality control is a crucial aspect of the manufacturing industry to ensure that the products produced meet quality standards and customer requirements. CV. XYZ, as a company engaged in the production of car seat covers, faces the problem of a high product defect rate, which results in increased rework costs, longer production time, and customer dissatisfaction. Based on preliminary data, a total of 214 defective units were recorded during the period from March to August out of a total production of 774 units. The three dominant types of defects include uneven stitching, peeling stitches, and material tearing or peeling. Therefore, this study applies the Seven Tools approach to analyze the factors causing defects and to provide improvement recommendations in order to reduce the product defect rate.